Lyrics and borrowed tunes of the American temperance movement - Sanders, Paul D., 1956- (University of Missouri Press, 2006)
"Systematically presents hundreds of lyrics set to borrowed tunes that were used by the American temperance movement (ca. 1840-1920) to further the cause of alcohol prohibition. Includes introductory text and musical notations for 32 borrowed tunes, grouped by song type"--Provided by publisher.